The Relationship Between Food Consumption and Nutritional Status in School-Age Children - Rr Lieliesnaini Octaviariani Sutoyo; Yoanita Indra Kumala Dewi; Mifta Wahyu Rafa Sakina; Ana Nur Filiya; Devi Kintan Putri Utari (Ficco Public Health Journal, 2026)
Background: Nutritional issues in school-age children remain a concern due to their impact on health, learning ability, and the quality of human resources. Food intake is a direct factor in determining nutritional status, but the relationship is not always linear. This study aimed to analyze the relationship between food consumption and nutritional status in school-age children. Methods: The study used an observational analytical design with a cross-sectional approach. The subjects were 32 school-age children aged 11–12 years at Modangan 5 State Elementary School Blitar, East Java. Food intake data, including energy, protein, fat, and carbohydrates, were obtained through a 24-hour food recall interview. Nutritional status data were determined based on anthropometric measurements of weight and height, which were then converted into a Z-score for body mass index for age (BMI/A). Data were analyzed descriptively and analytically using the Pearson correlation test. Results: The results showed that energy and macronutrient intake were not significantly related to the nutritional status of school-age children (p > 0.05). All correlation coefficients were in the very weak category. Conclusion: These findings indicate that the nutritional status of school-age children is influenced by various factors beyond daily food consumption.